INSTILLING MORAL VALUES THROUGH THE SONG 'PLEASE AND THANK YOU' IN EARLY CHILDHOOD EDUCATION - Survia, Desty (Lire Journal (Journal of Linguistics and Literature), 2025)
This study explores the moral values embedded in the song “Please and Thank You,” commonly used in early childhood education. Recognizing that early childhood education plays a significant role shaping children’s character and moral development, this study investigates the effectiveness of simple songs in conveying moral messages. The song “Please and Thank You” emphasizes the importance of politeness, manners, and social respect, using the magic words "please" and "thank you" as central elements of moral instruction. Using a qualitative descriptive approach based on content analysis, this study analyses the song’s lyrics through the lens of Kohlberg’s moral development theory, particularly focusing on the preconventional stage of moral reasoning in children. Since, it comes to songs designed for children, especially those in the preconventional stage, the lyrics often reinforce basic moral lessons such as distinguishing between good and bad behaviors, and the consequences of those behaviors. Findings suggest that the song not only enhances cognitive skills but also plays a crucial role in instilling values such as respect, kindness, and consideration for others. The results highlight the significant potential of songs as a medium for moral education, contributing to the development of positive moral. This study underscores the importance of incorporating moral value driven content in early childhood song education to foster a supportive environment for moral and social growth for children in their early age.